2010
DOI: 10.1309/ajcpqdqxj4fnrfqb
|View full text |Cite
|
Sign up to set email alerts
|

IMP3 Distinguishes Uterine Serous Carcinoma From Endometrial Endometrioid Adenocarcinoma

Abstract: Differentiating uterine serous carcinoma (USC) from endometrioid adenocarcinoma (EAC) could be problematic, especially in high-grade EACs and tumors exhibiting architectural variations. To address this issue, we evaluated 103 endometrial carcinoma cases using 4 immunomarkers, beta-catenin, IMP3, PTEN, and p53. Cases included 31 USCs, 57 EACs, and 15 mixed EAC-USCs. Of 31 USCs and 57 EACs, 8 and 9, respectively, were considered diagnostically difficult and challenging. beta-catenin was more frequently expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 30 publications
4
39
0
Order By: Relevance
“…Our results are consistent with those previously reported by other authors in histological studies, [12][13][14][15]19,20 where IMP3 was expressed in 90% of EC and EAIS cases, and most endometrial PSC (94%-100%) and endometrial CCC cases (57%-90%), but only a minority of EMAC (7%-25%). Nevertheless, we have noticed a trend for IMP3 to be more often expressed in EMAC with higher nuclear grade (NG 3) than those with a lower nuclear grade (NG 1 and 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with those previously reported by other authors in histological studies, [12][13][14][15]19,20 where IMP3 was expressed in 90% of EC and EAIS cases, and most endometrial PSC (94%-100%) and endometrial CCC cases (57%-90%), but only a minority of EMAC (7%-25%). Nevertheless, we have noticed a trend for IMP3 to be more often expressed in EMAC with higher nuclear grade (NG 3) than those with a lower nuclear grade (NG 1 and 2).…”
Section: Discussionsupporting
confidence: 93%
“…Re-expression of IMP3 is observed in tissue sections of several human malignancies, 16 including in situ and invasive endocervical adenocarcinoma and serous and clear cell carcinoma of endometrium. [13][14][15]19,20 To our knowledge, there is little experience with the use of IMP3 in LBC cytology containing AGCs or Ac. In a small study by Lastra et al, 12 the ICC expression and utility of IMP3 and ProEx C (a monoclonal antibody cocktail shown to be positive in dysplastic squamous and endocervical lesions) were assessed in a cohort of 34 cases diagnosed as atypical glandular cells of undetermined significance (AGUS) on cytology and found that IMP3 was positive in 80% of glandular neoplasms and negative in 93% nonglandular lesions/cases negative for squamous intraepithelial lesion (SIL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrioid carcinoma, however, has been shown to manifest TP53 gene mutation predominantly in its later stages and in higher grade tumors (Mhawech-Fauceglia et al, 2010). Many studies have investigated either TP53 gene mutation or p53 protein expression in mixed tumors, but correlation of the two has not been well described (Koul et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IMP3 or insulin like growth factor 2 mRNA binding protein 3 (IGF2BP3) is an RNA-binding oncofetal protein, which weighs 65 -70 KD and includes 580 amino acid and four K-homolog domains and is coded by the IMP3 gene on chromosome 7p11.5 and produces a 4350 base-pair mRNA (1,3). Overexpression of IMP3 (also known as L523S) has been reported in many cancers such as pancreatic carcinoma (4,5), lung adenocarcinoma (6-8), renal cell carcinoma (9-11), hepatocellular carcinoma, malignant melanoma (12), gastric cancer (13), ovarian carcinoma (14,15), urothelial carcinoma of bladder (16), cervical carcinoma (17,18), and testis cancer (19). It has been suggested as a prognostic marker in some cancers including breast cancer (20), neuroblastoma (21), and cervical cancer (18).…”
Section: Introductionmentioning
confidence: 99%